2013
DOI: 10.1139/cjfas-2012-0497
|View full text |Cite
|
Sign up to set email alerts
|

Regional-scale patterns in community concordance: testing the roles of historical biogeography versus contemporary abiotic controls in determining stream community composition

Abstract: The determinants of a local-scale biological community can include both abiotic and biotic factors acting at a variety of spatial and temporal scales. Previous studies have shown that the Precambrian Shield, a broad-scale geological feature, has distinct abiotic conditions and aquatic communities in lotic systems as compared with systems off-Shield. The relative importance of historical biogeography and postglacial colonization in Ontario versus the role of contemporary abiotic conditions has been debated in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Can fish or macroinvertebrate assemblages individually sufficiently represent the effects of anthropogenic stressors on river communities alone? Several studies (Griffith et al 2005;Paavola et al 2006;Flinders et al 2008;Infante et al 2009;Walters et al 2009;Bedoya et al 2011;Marzin et al 2012;Neff & Jackson 2013;Johnson & Ringler 2014;Pili ere et al 2014) that have compared the sensitivity of fish-and macroinvertebrate-specific indices in identifying main stressors suggest that two assemblages should be used simultaneously in bioassessment. Our analysis suggested that the screened metrics for fish and macroinvertebrates responded differently to the various environmental stressors.…”
Section: Metric Response To Environmental Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Can fish or macroinvertebrate assemblages individually sufficiently represent the effects of anthropogenic stressors on river communities alone? Several studies (Griffith et al 2005;Paavola et al 2006;Flinders et al 2008;Infante et al 2009;Walters et al 2009;Bedoya et al 2011;Marzin et al 2012;Neff & Jackson 2013;Johnson & Ringler 2014;Pili ere et al 2014) that have compared the sensitivity of fish-and macroinvertebrate-specific indices in identifying main stressors suggest that two assemblages should be used simultaneously in bioassessment. Our analysis suggested that the screened metrics for fish and macroinvertebrates responded differently to the various environmental stressors.…”
Section: Metric Response To Environmental Degradationmentioning
confidence: 99%
“…Despite the recommendations for assessments using fish and macroinvertebrate assemblages, less than a dozen studies (Griffith et al 2005;Paavola et al 2006;Flinders et al 2008;Infante et al 2009;Walters et al 2009;Bedoya et al 2011;Marzin et al 2012;Neff & Jackson 2013;Johnson & Ringler 2014;Pili ere et al 2014) have compared the responses of fish and macroinvertebrate assemblage-specific indices to stressors and suggested two taxonomic assemblages together are needed to determine streams and rivers condition. For example, Johnson and Ringler (2014) suggested that the major environmental variables affecting fish and macroinvertebrate assemblages differed, macroinvertebrate metrics better responded to substrate composition and land use, whereas stream morphometry and water chemistry were important variables for fish metrics, which was consistent with Walters et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Research on cross-taxon concordance and indicator groups is well developed in lotic systems (Heino et al 2009;Neff and Jackson 2013), especially in EU Countries where the classification of rivers' ecological status officially requires a multi-assemblage approach (Water Framework Directive;European Commission 2000). This approach, in turn, is needed to reach a synergy among the Water Framework Directive and the EU Habitat and Bird Directives (EC 1992(EC , 2009).…”
Section: Implication For River Managementmentioning
confidence: 99%
“…One way to assess the differences and similarities in the responses of groups of organisms is to evaluate community concordance, which measures the extent to which there is coherence or consistency among biotic assemblages, i.e., similarity in the characterization of stations based on the community structure of different groups of organisms (Jackson and Harvey 1993). Significant levels of community concordance have been found in assessments of BMI, fish, and other freshwater organism groups (e.g., diatoms, bryophytes, plankton, macrophytes) in both lakes and rivers (Kilgour and Barton 1999;Johnson and Hering 2010;Neff and Jackson 2013), though in some cases the strength of concordance was dependent on spatial or temporal scale of assessment (Allen et al 1999;Heino 2002;Paavola et al 2006;Bowman et al 2008). At small spatial scales, researchers have noted a lack of concordance among communities where local-scale drivers dominate and have suggested that each organism group responded to different environmental and anthropogenic pressures (Paavola et al 2003;Heino et al 2005;Infante et al 2009;Larsen et al 2012).…”
Section: Introductionmentioning
confidence: 99%